2022
DOI: 10.3390/cryst12070948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-Amino-1H-Tetrazole on Combustion Pyrolysis Characteristics and Kinetics of a Combustion Tear Gas Mixture

Abstract: Taking the combustion tear gas mixture as the research object, the system formula was optimized by adding a different mass fraction of 5-amino-1H-tetrazole(5AT). TG-DSC, a thermocouple, and a laser smoke test system were used to characterize the characteristic combustion parameters such as combustion temperature and velocity, as well as the end-point effects such as smoke concentration and particle size. Starink’s method, the Flynn–Wall–Ozawa method, and the Coats–Redfern method were used to evaluate the pyrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…TG-DSC, a thermocouple, and a laser smoke test system were used to characterize the combustion temperature and velocity, as well as the smoke concentration and particle size. Starink's method, the Flynn-Wall-Ozawa method, and the Coats-Redfern method were used to evaluate the pyrolysis kinetic parameters of the samples by Zhai, H. [10]. It was found that when the mass fraction of 5AT in the system was 10%, the maximum combustion temperature of the sample decreased by nearly 70 • C and the smoke concentration increased by 12.81%.…”
mentioning
confidence: 99%
“…TG-DSC, a thermocouple, and a laser smoke test system were used to characterize the combustion temperature and velocity, as well as the smoke concentration and particle size. Starink's method, the Flynn-Wall-Ozawa method, and the Coats-Redfern method were used to evaluate the pyrolysis kinetic parameters of the samples by Zhai, H. [10]. It was found that when the mass fraction of 5AT in the system was 10%, the maximum combustion temperature of the sample decreased by nearly 70 • C and the smoke concentration increased by 12.81%.…”
mentioning
confidence: 99%